2016
DOI: 10.4103/0970-9185.194778
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atrial natriuretic peptide infusion on intestinal injury in septic shock

Abstract: Background and Aims:The aim of this study is to assess the effect of atrial natriuretic peptide (ANP) on intestinal ischemia-reperfusion injury in septic shock.Material and Methods:A prospective randomized controlled, observer-blinded study was carried out in surgical Intensive Care Unit (ICU), University Hospital. Forty adult patients in septic shock were randomly divided into two groups, control group (Group C) received normal saline and ANP group (Group A) patients received ANP in the form of 1.5 mg vial ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…21,[76][77][78][79] Importantly, ANP exerts barrier-protective effects by reducing LPS-and TNF-a-induced increases in the permeability of endothelial cells and alleviating post-septic intestinal injury. 22,80 Furthermore, it has been documented that exogenous ANP has a protective role in terms of both neurofunctional improvement and infarct volume reduction in experimental models of ischemic stroke. 27 Corroborating these findings, our study showed that exogenous administration of ANP in a dose-dependent manner decreased cerebral infarct damage and ameliorated associated pneumonia in ISO mice.…”
Section: Discussionmentioning
confidence: 99%
“…21,[76][77][78][79] Importantly, ANP exerts barrier-protective effects by reducing LPS-and TNF-a-induced increases in the permeability of endothelial cells and alleviating post-septic intestinal injury. 22,80 Furthermore, it has been documented that exogenous ANP has a protective role in terms of both neurofunctional improvement and infarct volume reduction in experimental models of ischemic stroke. 27 Corroborating these findings, our study showed that exogenous administration of ANP in a dose-dependent manner decreased cerebral infarct damage and ameliorated associated pneumonia in ISO mice.…”
Section: Discussionmentioning
confidence: 99%
“…and adhesion molecules (vascular cell adhesion molecules, intercellular cell adhesion molecule-1, E-selectin, etc.) [ 17 , 28 31 ], suppressing LPS and TNF-α-induced increased permeability of endothelial cells [ 18 ], and alleviating post-septic intestinal injury [ 25 ]. However, the molecular mechanisms by which ANP modulates immune responses/immune cell activation are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental model of systemic LPS challenge-induced sepsis, ANP pretreatment could improve survival [ 24 ]. Furthermore, a prospective randomized controlled, observer‑blinded study found that ANP treatment could alleviate intestinal injury and reduce the length of intensive care unit (ICU) stay and mortality rate in patients with septic shock [ 25 ]. However, there are currently no reports of the effects of ANP on systemic LPS-induced endotoxemia-derived neuroinflammation and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%